Analytical expressions for the nuclear elastic scattering phase shifts in heavy ion collisions - Wong, Bernardine R. (Malaysian Journal of Science, 1995)
The elastic scattering of heavy ions is studied within the semiclassical framework. Analytical expressions are obtained for the elastic scattering phase shifts due to the nuclear potential using the one-turning-point Wentzel-Kramers-Brillouin approximation. The analytical expressions yield good agreement with respect to results obtained numerically through fully quantal calculations.